Protection Of Women's Rights in Marriage from The Perspective of Islamic Law and Criminology: A Study of Domestic Violence in Merangin Regency - Elvira Elvira; Hasbi Umar; Abdul Halim (Jurnal Smart Hukum (JSH), 2026)
This study examines the protection of women's rights within marriage through the integrated lens of Islamic law and criminology, with a focus on domestic violence (KDRT) cases in Merangin Regency, Jambi Province. Employing a qualitative normative-empirical approach, data were gathered through in-depth interviews with victims, law enforcement officers, Islamic legal scholars, and relevant government officials, supplemented by documentary analysis of court decisions, institutional reports, and applicable regulations. The findings reveal that KDRT in Merangin exhibits escalatory, cyclical, and multidimensional patterns, predominantly perpetrated by husbands who exploit asymmetric power relations rooted in patriarchal gender constructions. Implementation of Law No. 23 of 2004 on the Elimination of Domestic Violence faces significant structural barriers, including delayed reporting, revictimization, distorted interpretations of qiwāmah, and inadequate inter-institutional coordination. From an Islamic legal perspective, all forms of domestic violence fundamentally contradict the principles of mu'āsyarah bil ma'rūf, maqāṣid al-syarī'ah, and the universal prohibition of ẓulm. The study concludes that effective protection requires simultaneous transformation across legal, cultural-religious, and institutional dimensions, wherein Islamic law and positive law mutually reinforce rather than contradict one another